Hydrogen absorption and desorption in the Mg-Ag system - Urretavizcaya, Guillermina (2014)
We analyze hydrogen absorption and desorption in Mg and Mg?Ag compounds prepared by mechanical milling. The materials were obtained by processing mixtures of Mg or MgH2 with different proportions of Ag under Ar or H2 atmosphere.We observe that Ag and AgMg destabilize MgH2. In the first case the products of the reaction of Ag and MgH2 are AgMg and H2, in the second case MgH2 reacts with AgMg to give AgMg4 and H2. The first reaction was only observed in the forward direction, whereas the second one was registered in both directions. The impossibility to reverse the first reaction was attributed to poor kinetics and experimental limitations. The reversible destabilization induced by AgMg is low, MgH2 overall dehydriding enthalpy is reduced from 76.5 kJ/mol H2 to 69.1 kJ/mol H2. This last value allowed us to estimate the formation enthalpy of AgMg4 at _59.5 kJ/mol. Besides destabilization, a slight improvement in hydrogen absorption kinetics and a more noticeable enhancement in desorption kinetics has been observed in samples containing Ag as an additive. During thermal desorption, the dehydriding temperature decreases by 20 _C. In isothermal desorption experiments at 325 _C, the characteristic induction period of MgH2 without additive practically disappears, and the time to reach 50% of conversion decreases from 17 min to 5.4 min when silver is present. The changes in desorption kinetics could be attributed to AgMg or the interfaces MgH2/AgMg acting as nucleation sites for Mg.